2016
DOI: 10.1002/uog.15888
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal findings of hypertrophic cardiomyopathy in a severe case of Costello syndrome

Abstract: Prenatal findings of hypertrophic cardiomyopathy in a severe case of Costello syndromeCostello syndrome (CS) is a genetic disorder (HRAS mutations) characterized by a distinctive facial appearance, loose skin, developmental delay, cardiac abnormalities and tumor predisposition [1][2][3] . Major factor, which may severely affect neonatal prognosis, is cardiac abnormalities including arrhythmia, congenital defects and hypertrophic cardiomyopathy (HCM). Here we report prenatal findings of HCM in a severe case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Based on the clinical findings, the most likely diagnosis in our case may be Costello Syndrome (Table 3) 7 , and in 2016 by Uemura 8 ( Table 2). …”
Section: Discussionmentioning
confidence: 99%
“…Based on the clinical findings, the most likely diagnosis in our case may be Costello Syndrome (Table 3) 7 , and in 2016 by Uemura 8 ( Table 2). …”
Section: Discussionmentioning
confidence: 99%
“…Other findings include: nuchal thickening, ascites, hydrops, a small or absent stomach, short long bones, ulnar deviation of the wrists, macrosomia, macrocephaly, hepatomegaly, cardiomyopathy, and tachycardia. 1,[3][4][5][6][7][8][9] The p.Gly12Val (NM_005343.3(HRAS):c.35_36 delinsTT) pathogenic variant is a recurring CS variant that has been associated with an early, lethal form of this condition. 8 To date, 8 cases of CS caused by this particular variant have been reported, all presenting with lethal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9] The p.Gly12Val (NM_005343.3(HRAS):c.35_36 delinsTT) pathogenic variant is a recurring CS variant that has been associated with an early, lethal form of this condition. 8 To date, 8 cases of CS caused by this particular variant have been reported, all presenting with lethal outcomes. 4,5,9,10 This report is the ninth case, with initial fetal presentation of hepatic tumor, which has never previously been described as an antenatal manifestation of CS.…”
Section: Introductionmentioning
confidence: 99%
“…Only isolated cases have been reported, for example, in fetuses of genetic disorders. 1 In this study, we describe HCM identified by mid-pregnancy ultrasound in a prenatal case with Noonan syndrome (NS), and this association has seldom been reported.The work was carried out according to the principles of the Declaration of Helsinki and approved by the ethics committee of Guangzhou Women and Children Medical Center. Written informed consent was obtained from the family regarding artificial pregnancy interruption.…”
mentioning
confidence: 98%
“…Only isolated cases have been reported, for example, in fetuses of genetic disorders. 1 In this study, we describe HCM identified by mid-pregnancy ultrasound in a prenatal case with Noonan syndrome (NS), and this association has seldom been reported.…”
mentioning
confidence: 98%